(untitled) (Global Scientific Review, 2022)
In this article, in the process of environmental assessment of urban development solutions adopted in the development of the master plan of the city of Pop, the identification of existing environmental problems in the town, the assessment of the adequacy and effectiveness of the proposed solutions and proposals to gradually achieve a favorable ecological situation in the project, and the state of the environment in the case of the implementation of the master plan prediction works are analyzed.